Phenocam - Red Chromatic Coordinates (RCC) Composite Image Mean Values from Skogaryd Stordalen Catchment, Mast 5.9m Phenocam 01 - Skogaryd Research Catchment (University of Gothenburg, 2022)
Red Chromatic Index (RCI) also known as Red Chromatic Coordinate (RCC) is a measure of the redness of vegetation. It is calculated from daily averaged RGB (Red, Green, Blue) composites values of digital images captured by PhenoCams.
Skogaryd Research Catchment (2022). Phenocam - Red Chromatic Coordinates (RCC) Composite Image Mean Values from Skogaryd Stordalen Catchment, Mast 5.9m Phenocam 01, 2014-01-01–2014-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/23qwW2k51wc5NmLNQhyNyZG5
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap